Percutaneous radiofrequency‐assisted liver partition versus portal vein embolization before hepatectomy for perihilar cholangiocarcinoma. Issue 1 (3rd February 2020) - Melekhina, O.; Efanov, M.; Alikhanov, R.; Tsvirkun, V.; Kulezneva, Y.; Kazakov, I.; Vankovich, A.; Koroleva, A.; Khatkov, I.
Graphical Abstract: Abstract: Background: Percutaneous radiofrequency-assisted liver partition with portal vein embolization in staged liver resection (PRALPPS) represents an alternative to portal vein embolization (PVE) followed by major liver resection in patients with perihilar cholangiocarcinoma. Methods: This was an observational case–control study. Both procedures were applied in patients with a future liver remnant (FLR) volume of less than 40 per cent. The main end points of the study were short-term morbidity and mortality for the two procedures. The study also compared the efficacy of the preresection phases estimated by kinetic growth rate (KGR), time interval and degree of hypertrophy of the FLR. Results: The first phase (preresection) was completed in 11 and 18 patients, and the second phase (resection) in nine and 14 patients, in the PRALPPS and PVE groups respectively. Major morbidity after the first stage did not differ between the groups. There were no differences in blood loss, severe morbidity or liver failure rate after the second stage, with no deaths. The mean KGR of the FLR after the preresection phase for PRALPPS was 3·8 (0·6–9·8) per cent/day, and that after PVE was 1·8 (0–6·7) per cent/day ( P = 0·037). The mean time interval for FLR hypertrophy in the PRALPPS and PVE groups was 15 (6–29) and 20 (8–35) days respectively ( P = 0·039). Conclusion: S hort-term outcomes were similar for PRALPPS and PVE in terms of safety. Remnant hypertrophy was achieved more rapidly by PRALPPS.